The influence of the principal's leadership and the role of the committee on the teacher discipline - Marini Sartika; Happy Fitria; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to determine the effect of the principal's leadership and the role of the committee on teacher discipline at SMA Negeri Muara Enim . This research uses quantitative methods with correlational research type. The population was 179 teachers who were in sub-district 7 Muara Enim Regency with a sample of 124 teachers. The sampling technique is a sampling area. Data collection techniques use questionnaires and documentation. Data were analyzed using correlation analysis techniques and multiple regression . The results showed that: (1) The leadership of the principal has a significant and significant effect on the discipline of SMA teachers in Muara Enim Regency (2) The role of the committee has a significant and significant effect on the discipline of teachers of SMA Negeri in Muara Enim Regency; and (3) The leadership of the principal and the role of the school committee together have an effect and are significant on the performance of SMA teachers in Muara Enim Regency.